Stability and Superstability of Ring Homomorphisms on Non-Archimedean Banach Algebras - M. Eshaghi Gordji; Z. Alizadeh (Abstract and Applied Analysis)
Using fixed point methods, we prove the superstability and generalized Hyers-Ulam stability of ring homomorphisms on non-Archimedean Banach algebras. Moreover, we investigate the superstability of ring homomorphisms in non-Archimedean Banach algebras associated with the Jensen functional equation.